From de lipid hypothesis to the carbo-oily model - Montero, Julio César (Revista del Hospital Italiano de Buenos Aires, 2014)
The epidemic of cardiovascular disease (CVD) was -and still is in media- attributed to dietary factors present in natural foods, mainly saturated fat and cholesterol. The conclusions of the Seven Countries Study led to the ‘lipid hypothesis’, which was applied even when the results of succeeding studies did not validate it. The proposed changes aimed at limiting the intake of saturated fats and cholesterol from healthy foods (meat, dairy, eggs). These recommendations were imperfect, even to achieve the objectives of the lipid hypothesis. Saturated fats from meat and dairy products were being inadvertently replaced by hydrogenated oils and solid fats (margarines and industrial shortening) and were used in the preparation of processed food containing carbohydrates (proposed to replace the calories from saturated fats). Statistics show increased CVD in countries that have adopted this new model and the most recent studies have failed to substantiate the claims of the lipid hypothesis. Cardiovascular effects of fatty acids incorporated as animal fat substitutes, especially those known as essential, should be further investigated
Keywords: cardiovascular disease and nutrition; saturated fat and cardiovascular disease; animal fat and cardiovascular disease; animal food and atherosclerosis